2006
DOI: 10.1200/jco.2006.06.1572
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Temozolomide in Relapsed or Refractory High-Risk Neuroblastoma: A Joint Société Française des Cancers de l’Enfant and United Kingdom Children Cancer Study Group–New Agents Group Study

Abstract: Temozolomide shows activity in heavily pretreated patients with NB, and deserves further evaluation in combination with another drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…We investigated whether these effects would enhance the cytotoxicity in the treatment of cancers with commonly used chemotherapeutic agents. We combined LB1.2 with temozolomide (TMZ), a DNA-methylating chemotherapeutic drug, to treat glioblastoma multiforme (GBM) (11) and neuroblastoma (NB) (12) xenografts in the mouse models. We also combined LB 1.2 with Doxorubicin (DOX), a DNA intercalating chemotherapeutic drug, (13) in GBM xenografts to study whether the effect depends on the specific mechanism of the cytotoxic agent.…”
Section: Medical Sciencesmentioning
confidence: 99%
“…We investigated whether these effects would enhance the cytotoxicity in the treatment of cancers with commonly used chemotherapeutic agents. We combined LB1.2 with temozolomide (TMZ), a DNA-methylating chemotherapeutic drug, to treat glioblastoma multiforme (GBM) (11) and neuroblastoma (NB) (12) xenografts in the mouse models. We also combined LB 1.2 with Doxorubicin (DOX), a DNA intercalating chemotherapeutic drug, (13) in GBM xenografts to study whether the effect depends on the specific mechanism of the cytotoxic agent.…”
Section: Medical Sciencesmentioning
confidence: 99%
“…TEM has recently been evaluated as a single-agent for neuroblastoma (3,13). Similar to the case with high-grade glioma, responses and prolonged stable disease are seen in a subset of patients.…”
mentioning
confidence: 99%
“…One potentially promising regimen is the combination of the DNA methylating agent temozolomide with the topoisomerase I inhibitor irinotecan. Both drugs have single-agent activity against neuroblastoma (2,3), and preclinical studies have shown that administration of TEM followed by IRN results in schedule-dependent synergy against mouse models of this disease (4). Based on encouraging preliminary reports of this combination in children with relapsed solid tumors (5 -7), the Children's Oncology Group is now conducting a national phase II trial of this drug pair to define its activity for neuroblastoma in first relapse.…”
mentioning
confidence: 99%
“…Phase II studies showed efficacy of topotecan in combination with cyclophosphamide (5) or with vincristine and doxorubicin (6), and of temozolomide as monotherapy (7). Topotecan alone or in combination with cyclophosphamide showed response rates up to 76% in previously untreated patients (8) and 64% in patients with refractory or relapsed neuroblastoma, in combination with vincristine and doxorubicin (TVD; ref.…”
mentioning
confidence: 99%